CD96 targeted antibodies need not block CD96-CD155 interactions to promote NK cell anti-metastatic activity. (4th May 2018) - Roman Aguilera, Amelia; Lutzky, Viviana P.; Mittal, Deepak; Li, Xian-Yang; Stannard, Kimberley; Takeda, Kazuyoshi; Bernhardt, Günter; Teng, Michele W. L.; Dougall, William C.; Smyth, Mark J.
ABSTRACT: CD96 is a transmembrane glycoprotein Ig superfamily receptor, expressed on various T cell subsets and NK cells, that interacts with nectin and nectin-like proteins, including CD155/polio virus receptor (PVR). Here, we have compared three rat anti-mouse CD96 mAbs, including two that block CD96-CD155 (3.3 and 6A6) and one that does not block CD96-CD155 (8B10). Using flow cytometry, we demonstrated that both mAbs 3.3 and 6A6 bind to the first Ig domain of mouse CD96 and compete with CD155 binding, while mAb 8B10 binds to the second Ig domain and does not block CD155. While Fc isotype was irrelevant concerning the anti-metastatic activity of 3.3 mAb, in four different experimental metastases models and one spontaneous metastasis model, the relative order of anti-metastatic potency was 6A6 > 3.3 > 8B10. The metastatic burden control of all of the anti-CD96 clones was highly dependent on NK cells and IFN-γ. Consistent with its inability to block CD96-CD155 interactions, 8B10 retained anti-metastatic activity in CD155-deficient mice, whereas 3.3 and 6A6 lost potency in CD155-deficient mice. Furthermore, 8B10 retained most of its anti-metastatic activity in IL-12p35-deficient mice whereas the activity of 3.3 and 6A6 were partially lost. All three mAbs were inactive in CD226-deficient mice. Altogether, these data demonstrate anti-CD96 need not block CD96-CD155 interactions (ie. immune checkpoint blockade) to promote NK cell anti-metastatic activity.